In silico screening and experimental validation of Carissa carandas L. extract against cyclophosphamide-induced cardiotoxicity in Wistar rats - Roopadevi Desaipatti, Namit Kudatarkar, Sachin Gudasi (Journal of Applied Pharmaceutical Science, 2025)
The aim of this study was to evaluate the cardioprotective effects of Carissa carandas L extract against cardiotoxicity which was induced by cyclophosphamide (CP) in male Wistar rats. The target proteins related to C. carandas L. were selected from super pred databases and constructed Compound–targets–pathways network. General observation determination of cardiac markers enzymes, heart tissue homogenate analysis, body weight assessment, electrocardiogram (ECG) pattern analysis, and histopathological studies were conducted. Network pharmacology analysis identified the PI3K-Akt signaling pathway as a key pathway modulated by the compound, with a false discovery rate of 2.78E-05 and a strength of 1.21. A protein-pathway compound interaction network was established, highlighting MAPK1, NOS3, EP300, and STAT3 as having the highest edge counts at 14, 11, 9, and 9. CP administration significantly decreased body weight and increased heart weight. CP elevated levels of biomarker enzymes like creatine kinase isoenzyme MB, aspartate transaminase, alanine transaminase, and alkaline phosphatase. Furthermore, CP-induced rats showed significant deviations in these parameters compared to the normal group (heart rate: 264.83 ± 3.06 beats per minute; P-R interval: 0.064 ± 0.0001 msec; Q-T interval: 0.068 ± 0.0003 msec; R wave amplitude: 0.24 ± 0.004 mV), indicative of cardiotoxicity and significantly reduced superoxide dismutase (SOD) activity, elevated cardiac malondialdehyde levels and decreased glutathione levels. The histopathological examination provided evidence indicating a potential cardioprotective effect, as it revealed a decrease in the severity of cellular damage within the myocardium. These findings suggest the potential therapeutic utility of C. carandas L in managing chemotherapy-induced cardiotoxicity, highlighting its significance in improving the quality of life and treatment outcomes for cancer patients.
Keywords: Cyclophosphamide, cardiotoxicity, Carissa carandas L, simvastatin, cardioprotective